Interaction of sodium alginate with cetyltrimethylammonium bromide in aqua-organic mixed solvents: influence of temperatures and compositions. Issue 7 (1st June 2022) - Hoque, Md. Anamul; Mahbub, Shamim; Khan, Mohammed Abdullah; Eldesoky, Gaber E.
Abstract: Herein, the interaction of sodium alginate (SA) with cetyltrimethylammonium bromide (CTAB) has been studied in aqueous solution as well as in aqua-organic mixed solvents at varying temperatures using conductivity measurements. Ethylene glycol (EG), dimethyl formamide (DMF), 1, 4-dioxane (DO), and acetonitrile (AN) were used as organic solvents. The CMC values for SA + CTAB system in 10% (v/v) mixed solvents follow the order: CMCwater + DO > CMCwater + DMF > CMCwater + AN > CMC water + EG > CMCwater . The CMC values for the SA + CTAB system in aqueous medium indicate that SA lowers the CMC of pure CTAB. The higher CMC values in all the solvent mixtures may be due to the decrease of the dielectric constant and cohesive energy density of water. The interaction of SA with CTAB is affected significantly by the change in temperature which is attributed to changes in hydration of SA and CTAB. The negative values of free energy of micellization ( Δ G m o ) for the SA + CTAB system imply the spontaneous aggregation phenomenon and the negative Δ G m o values in H2 O and 10% (v/v) mixed solvents follow the trend: Δ G m o (H2 O) > Δ G m o (water + EG) > Δ G m o (water + DMF) > Δ G m o (water + DO) > Δ G m o (water + AN). The values of free energy changes of transfer ( Δ G m, t o ) were also evaluated for the shift of SA + CTAB mixture from water to aqua-organic mixed solvents and discussed the results in detail. The binding interactions of SA with CTAB are proposed to be hydrogen bonding, ion-dipole, and hydrophobic interactions. The enthalpy-entropy compensation of SA + CTAB systems was assessed and illustrated in detail. Graphical Abstract: